Diversity of underutilized vegetables and fruit in Sri Lanka: Prioritization for collection, conservation, genetic improvement, and promotion - Pushpakumara, Gamini; Silva, Renuka; Borelli, Teresa; Hunter, Danny; Ariyarathne, Mojith; Eeswara, Janaki; Fonseka, Ramya; Fonseka, Hemal; Karunarathne, Asha; Dissanayake, Samantha; Lowe, Ayesh; Rankoth, Lalith; et al. (2023)
Despite their crucial role in combating hunger, malnutrition, and poverty, many plant species cultivated as fruits, vegetables, roots, and tuber crops remain neglected and underutilized worldwide, and Sri Lanka is no exception. Integrating these crops into farming systems has the potential to create nutrient-dense, climate-resilient, and sustainable agricultural practices. The study titled "Diversity of underutilized vegetables and fruit in Sri Lanka: prioritization for collection, conservation, genetic improvement, and promotion" highlights the significance of underutilized vegetables and fruits in Sri Lanka's agricultural biodiversity. These often-overlooked crops possess unique nutritional and agronomic traits that could benefit both farmers and consumers. However, they have been overshadowed by more commonly cultivated species and varieties. To safeguard the genetic diversity and potential contributions of these underutilized crops to food security and nutrition, the study emphasizes the need for prioritizing their collection and conservation. Preserving their genetic resources enables researchers and farmers to access a broader range of traits, enhancing resilience to environmental challenges. Additionally, the research underscores the importance of genetic improvement efforts to boost the productivity and adaptability of underutilized vegetables and fruits. Breeding programs focused on priority species can lead to the development of new cultivars with desirable traits, such as increased yield, disease resistance, and improved nutritional content. Moreover, promoting underutilized crops is essential to raise awareness among consumers, retailers, and policymakers about their nutritional benefits and economic potential. By creating market demand and integrating these crops into agricultural systems, their sustainable cultivation and utilization become more viable. In summary, recognizing and prioritizing the diversity of underutilized vegetables and fruits in Sri Lanka is crucial. Through strategic collection, conservation, genetic improvement, and promotion efforts, these crops can significantly contribute to enhancing food security, preserving biodiversity, and supporting sustainable agricultural practices in the country.